Steady as She Goes: Remote Work Benefits Daily Goal Progress Through Reduced Energy Variability - Bennett, Andrew; Keeler, Kathleen; Campion, Emily; Keener, Sheila (Organization Science, 2026)
As the prevalence and allowance of remote and hybrid work evolves, research has shown consistently mixed findings about how work location is related to worker energy and perceptions of daily performance. We aim to resolve this ambiguity by integrating Affective Events Theory with ideas about emotion dynamics to develop new theorizing explaining why energy variability, rather than mean energy level, is an important predictor of daily goal progress. We test our hypotheses using a sample of 219 employees from one organization allowing remote and hybrid work, capturing individual hourly energy levels for five consecutive workdays (4,812 hourly observations). Our results show that on days when employees work from home (vs. onsite), they have lower energy variability, which enables them to make more progress towards their goals and achieve their goals at a faster rate than expected that day. Moreover, we show that this effect is stronger when employees have higher remote work intensity (i.e., work from home more often). Our findings are robust to a number of controls (e.g., children at home, work location choice, industry). Practically, workers experience about 33% less energy variability on days working from home compared to onsite, and a one-point reduction in energy variability yields 26% higher goal progress and 31% higher goal progress velocity. Overall, this study advances theory on the relationship between daily work location, human energy, and goal progress, and has immediate practical implications for employees, teams, and organizations as they continue to navigate the remote and hybrid era of work.